CHIRAL SEPARATION OF CETIRIZINE ENANTIOMERS BY CYCLODEXTRIN MEDIATED CAPILLARY ELECTROPHORESIS - Gabriel Hancu; Monica Budău; Lajos Attila Papp; Aura Rusu; Eleonora Mircia (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Chiral separation cetirizine, a second generation H1 antagonist was studied by cyclodextrine (CD) mediated capillary electrophoresis. The influence on the separation of several parameters including pH and concentration of the background electrolyte (BGE), CD type and concentration, applied voltage and temperature were studied and the electrophoretic and analytic parameters were optimized. The best conditions for the chiral separation were obtained using 25mM disodium hydrogeno-phosphate – 25mM sodium didydrogeno-phosphate (1:1) as BGE, 5mM sulfobuthyl ether- β-CD as chiral selector, a voltage of + 20kV, temperature of 20°C, injection pressure/time of 50mbar/ 1sec, UV detection at 230nm. The analytical performance of the method was evaluated. The proposed method was successfully applied to the enantioselective assay of cetirizine in pharmaceutical formula-tions. CE proved to be a rapid, speciﬁc, reliable and cost-effective method for the chiral separation of cetirizine enantiomers and can be useful for laboratories performing routine analysis.